E-HR AUTOMATED RESUME ANALYSIS - MUHAMMAD FATEH TEH, FAZIRA AMIRAH (IRC, 2020)
Every company or organization consists of one human resources department. The purpose of this study is to analyze the problems that always been confronted by the human resources department. Specifically, the challenges that being faced by every human resource which is handling a massive amount of resume. With this paper, it will introduce a new implementation and execution of the existing system which aims to reduce the human resources workload. Traditionally, human resources mostly will rely on the personal interviews and focus on questioning the candidates for psychology. Usually it will take more steps to finally find the most suitable candidate for the job position. Every step taken in recruiting required a large amount time and efforts to process. Nowadays, most of the company or organization acquire the recruiting tool or system to increase efficiency of human resource department. However, the existing tool and system consist of several deficiencies. With this research and study proposed will eliminate the challenges faced. To carry out the preliminary studies, literature review and observing the potential company and organization will be done. The purpose of this project is to achieve a e-HR automated resume analysis that can be integrated with the web application services. Addition to that the automation process will automate an accurate analysis that shall be able to match between the job requirement needed and the candidate’s resume information. As for the system development methodology, SDLC technique will be implement with the used of RAD methodology model with that a development could be completed within a certain period. Tools and software that involves in the development process is UiPath and Microsoft Visual Studio. This proposed solution, surely will bring benefits and advantages to the human resources industry in achieving wider market by using web services and RPA technology. The results are human resources or recruiter can use this system to easily extract data of suitable candidate without spending too much time on screening the resume.